THE DAYA LINUWIH, POLITICAL ACTOR CANDIDATE OF THE SOLO PILKADA - Betty Gama; Bani Sudardi; Wakid Abdullah; Mahendra Wijaya, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2017)
The election of regional heads (Pilkada) is an election to elect the mayor and deputy mayor over the next five years. The pilkada candidates are not only known by the society, but also have extrasensory power (in Indonesian language is daya linuwih). Daya linuwih is interpreted as an advantage, excess or strength of the political actors, in order to win the Solo Pilkada in 2010.The activities of Pilkada candidates in various campaigns attract not only the society, but also the mass media. The Solopos newspaper as a local media in Solo City have an important role in framing the current political events and increasing the popularity and electability of political actors. Pilkada that occurred in 2010 was different in previous years, if seen from the behavior of candidates when campaigning. Election Candidate couple (JokoWidodo- FX Rudi Rudyatmo) has used the Javanese cultural approach to influence the society.The behavior of candidates, who are polite, caring, respectful and respectful to the elderly and the poor society were the forces of attraction or extrasensory power (daya linuwih).The purpose of this research is to find out the frames that appear in Solopos newspaper related to the campaign by the political actor candidates of Pilkada. This research uses qualitative research method, with framing analysis approach. Framing analysis is used to examine the text of Solopos newspaper. The object of this research is the election campaign news relating to extrasensory power, which concerns andhapasor, blusukan, and self-imaging. The result shows that a political candidate ofJokoWidodo - FX HadiRudyatmo, who joined in Andhap Asor Coalition, which uses the concept of andhap asor,blusukan and self-imaging have won the election (Pilkada) campaign. It is based on Javanese culture.